ПРОФЕСІЙНО-ПЕДАГОГІЧНА ПІДГОТОВКА ВЧИТЕЛЯ В СПАДЩИНІ С. Й. ГЕССЕНА (1887–1950) - Киричок, Інна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Предметом дослідження автора – концепція професійно-педагогічної підготовки вчителів відомого російського педагога С. Й. Гессена. Велику увагу приділено характеристиці вимог до вчителя, які висуває мислитель. Доведено, що С. Й. Гессен одним з перших в педагогічній думці розглядав умови успішної діяльності вчителя – концептуальне педагогічне мислення. Ідеї цілісного формування особистості вчителя, які обстоював вчений, суголосні парадигмі сучасної системи освіти. Дослідження спадщини С. Й. Гессена дозволило автору статті обґрунтувати умови ефективності професійної підготовки вчителя, які він вважав основоположними. Предметом исследования автора – концепция профессионально-педагогической подготовки учителей известного российского педагога С. И. Гессена. Большое внимание уделено характеристике требований к учителям, которые выдвигает мыслитель. Доказано, что С. И. Гессен одним из первых в педагогической мысли рассматривает условия успешной деятельности учителя – концептуальное педагогическое мышление. Идеи целостного формирования личности учителя созвучны парадигме современной системы образования. Исследование наследия С. Й. Гессена позволило автору статьи обосновать условия эффективности профессиональной подготовки учителя, которые он считал осново-полагающими. The subject of author’s investigation is the concept of professionalpedagogical training of teachers of famous Russian teacher S. I. Geissen. Great attention is paid to the characteristics of the requirements for teachers which are said by thinker. It is known that S. I. Geissen the first who considered the conditions of successful activity of a teacher in pedagogical thought-conceptual pedagogical thinking. Ideas integral formation of the individual teacher who defended the scientist, in unison with the paradigm of the modern education system. Research S. I. Gessen’s heritage has allowed the author to justify the conditions of efficiency of vocational teacher training, which he considered fundamental. S. Hessen’s ideal teacher in becoming a teacher and humanist, pupil-master, with an active lifestyle, creative teacher who has a set of pedagogical skills, strong-willed and human qualities, which uses a variety of teaching methods, and has its own style of communication and teaching methods.